La legge sulle donne. Perché cambia, come cambia - Renzaglia, Fabrizio; Renzaglia, Beatrice; Santomauro, Sandra (Il sogno della farfalla, 2020)
In may 1981 the law which justified feminicide, sexual violence (and infanticide) as ‘honoris causa’ and established irrelevant penalties or acquittal in case of ‘shotgun wedding’, was abrogated in Italy. In April 1981 the fourth volume of Fagioli’s theoretical work, Child woman and man’s transformation, had already been published in its first edition. This article discusses the stages leading to the parliament’s decision following a legislative procedure which lasted for 26 years. The primum movens considered is Franca Viola’s story and the tumultuous events of the 70s.The authors particularly draw the attention on the development of a new movement represented in that time by Fagioli’s Human Birth theory. This absolute novelty has allowed to comprehend how the historically considered ‘outsiders’ – women, children and foreigners – have always been considered as humans to a lesser extent until recently.